Pedestrian decision-making in urban street crossing analyzing crosswalks and overpass bridge utilization in East Avenue, Quezon City - Par, Bryll Edison C. (College of Architecture, University of the Philippines Diliman, 2025)
Street crossing in urban environments poses significant safety risks to pedestrian due to their direct interaction with vehicular traffic. Despite the presence of various safe crossing infrastructure, such as crosswalks and overpass bridges, their utilization and the factors influencing pedestrian decision-making remain largely undefined in the Philippine context. This study examines pedestrian decision-making in urban street crossing along East Avenue, Quezon City , by analyzing crosswalk and overpass bridge utilization and identifying factors influencing infrastructure choice. Mixed method was employed, combining on-site observation through video recording, pedestrian volume counts, and surveys. Pedestrian decision-making influencing factors, including gap and yielding acceptance, as well as pedestrian needs influencing factors related to travel characteristics and environmental attributes, were examined. Findings show that overpass bridges are significantly more utilized than crosswalks. Pedestrians noted that at-grade crossings are more convenient due to time efficiency, reduced physical effort, and shorted travel distance, while overpass bridges are safer and much preferred but are often avoided because of steep stairs, limited accessibility, additional travel time, and discomfort. The study concludes that pedestrian infrastructure choice is primarily driven by convenience, accessibility, and perceived efficiency, highlighting the need for pedestrian-centered planning approaches to improve safety and mobility.